(untitled) (Research, Society and Development, 2022)
The aim of this study is to evaluate the functional status on the clinical outcome of elderly hospitalized with Covid-19. This is an observational, quantitative and descriptive research, which was carried out at the Lauro Wanderley University Hospital (LWUH) from May to August 2021. The study population consisted of elderly people treated at the HULW’s Infectious Parasitic Diseases and Covid-19 ward, and the inclusion criteria were: age group over 60 years, of both sexes, with a confirmed clinical diagnosis of Covid-19. The instruments for data collection included a form developed by the researchers, covering sociodemographic issues, clinical and physical aspects related to the level of mobility, and the Katz index to assess basic activities of daily living, as well as the clinical outcome of the participants in the scope of hospital. Eleven elderly people participated in the research. Of these, 66.3% (n=7) were male, with a mean age of 73.90 (±7.68). There was a statistically significant difference in the degree of mobility, in which the patients who died were restricted to the bed, while those who were discharged from the hospital walked. It is concluded that Covid-19, because it is a disease that affects multisystems, it impacts even more negatively elderly people with functional decline.